Analisis Pengaruh Mekanisme Corporate Governance Dan Audit Tenure Terhadap Integritas Laporan Keuangan - Agnes Dwi Santia; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This research aims to provide empirically the effect of corporate governance mechanism and audit tenure to the integrity of financial statements. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2015-2018. Integrity of financial statements variables are measure by market book ratio using. The sample in this study was determined by purposive sampling method. The type of data used is secondary data obtained from www.idx.co.id as well as company website and other sites related to research. The analytical method used is Multiple Regression Analysis. The results of this study indicates that only audit committees has significant influence to increasing integrity of financial statement. But managerial ownership, independen directors and audit tenure don’t influence on the integrity of financial statement